Experimental study of performance of repair mortar: Evaluation of in-situ tests and correlation analysis. (September 2020) - Shi, Jinyan; Liu, Baoju; Qin, Jiali; Jiang, Junyi; Wu, Xiang; Tan, Jinxia
Abstract: This study investigated the performance of repair mortar incorporating mineral admixtures under different curing conditions. The mechanical properties, hydration degree and pore characteristics were taken as basic properties, the transport properties of capillary water absorption, chloride ion diffusivity and gas permeability were measured. The results show that mineral admixture and the external curing conditions have a great influence on the internal pore structure and transport performance of the mortar. In addition, surface gas permeability and water intentional spraying tests were used to evaluate the surface quality of cement-based material. It was found that these indices of in-situ tests have a strong correlation with the pore structure, mechanical properties and permeability of the mortar. Meanwhile, some new equation was established showing the correlation between surface quality index of in-situ tests and the laboratory performance of mortars, in order to establish a generalized approach. This provides an effective approach to solve the in-situ evaluation of the quality and durability of cement-based materials. Highlights: Curing conditions was a vital factor affecting mortar hardened performance. Correlation between air-void system and permeability was significant. The in-site evaluation indicator for repairing mortar was proposed. The usability of the SGP and WIS tests were verified of multiple mineral admixture mortars under different curing conditions. CWA, RCM and the gas permeability results were strongly related.